Effects of different exercise interventions on bone mineral density in elderly postmenopausal women: a network meta-analysis - Ma, Mingyu; Su, Wentao; Liu, Dansong (Frontiers in Physiology, 2025)
BackgroundVarious exercise interventions have been widely applied to enhance site-specific bone mineral density in menopausal females. This network meta-analysis aims to assess and compare the impact of these interventions on improving BMD in this demographic.MethodsA systematic search of PubMed, EMBASE, Cochrane Library, and Web of Science was made up to 4 December 2024 to detect randomized controlled trials (RCTs) comparing continuous endurance training whole-body vibration resistance training multicomponent training mind-body training intermittent training and combined training against control interventions. Primary outcomes included lumbar spine bone mineral density and femoral neck bone mineral density while secondary outcomes covered whole body bone mineral density and total hip bone mineral density A Bayesian random-effects NMA was performed.ResultsFifty-five RCTs involving 3,453 participants were included. Compared with the control group, MCT demonstrated greater efficacy in improving FNBMD (mean difference [MD] 0.02; 95% credible interval [CrI] [0.01, 0.04]). Based on the surface under the cumulative ranking (SUCRA), MBT ranked highest for LSBMD (75.9%), CT for WBBMD (77.6%), and MBT for THBMD (60.7%), suggesting potential benefits of these interventions.ConclusionThis study suggests that MBT, MCT, and CT may contribute to improving BMD in elderly postmenopausal women. However, further rigorously designed RCTs are warranted to validate these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025636067.